Ekstrakurikuler Paduan Suara Di MAN 2 Kota Padang - Shelliana Putri; Syeilendra Syeilendra (Institut Nalanda, 2023)
This study aims to describe the process of extracurricular implementation of Choir in MAN 2 Padang City. This type of research research is qualitative research with descriptive methods. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data were collected through literature study, observation, interviews and documentation. The steps of analyzing data are data reduction, data presentation and conclusions. The result of this study is that the planning of choir extracurricular activities at MAN 2 Kota Padang is carried out through several stages, namely first the coach prepares choir members by recruiting every new school year, then determines the rehearsal schedule, after that the coach prepares the material and chooses songs before starting the practice. The implementation of extracurricular choir is carried out by means of trainers who always teach students one by one according to the division of voice qualifications and in providing material the trainer demonstrates the tone and rhythm of the song per sentence or perphrase until students understand and memorize the tone of the song material. At the end of each meeting the coach always gives an evaluation, the coach tells the parts that must be improved and the coach always reminds about the importance of vocal technique. In addition to evaluating the coach's voice also provides an evaluation of the training process, the coach asks students to be serious in each exercise so that the coach does not need to repeat mistakes in that part only.